Applications of bacterial cellulose as precursor of carbon and composites with metal oxide, metal sulfide and metal nanoparticles: A review of recent advances. (10th February 2017) - Foresti, M.L.; Vázquez, A.; Boury, B.
Highlights: The nanostructure of BC is highly suitable for the preparation of inorganic materials-BC composites. Process conditions affect bacterial cellulose production and properties. Chemical post-treatments of BC may impact on its assemblies with inorganic phases. Composites of BC with metal oxide, metal sulfide and metal nanoparticles are reviewed. Conversion of BC into carbon and integration with inorganic phases is described. Abstract: This mini review is limited to very recent studies (last 5–10 years) on two major issues, concerning: the production and physical/chemical modification of bacterial cellulose (BC), and its transformation into carbon and integrated synthesis of metal oxides (TiO2, ZnO, Fe3 O4, etc.), metal sulfide (ZnS, CdS, etc.) and metal nanoparticles (Au, Ag, Pt, Pd, etc.) within bacterial cellulose nanoribbons network. We believe that the crossover of these two domains could be of considerable interest in the view of improving the performance of materials prepared with bacterial cellulose. The diversity of these nanomaterials allows targeting of many very different properties/applications: electrochemical devices, catalysis and photocatalysis, sensors, etc. After an introduction to the most important chemical and physical characteristics of BC, production parameters, and its physical and chemical modifications, we review the use of BC as a precursor of inorganic materials like carbon and composites with metal or inorganic nanoparticles.